2020
DOI: 10.1101/2020.02.09.940403
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nyctinastic thallus movement in the liverwortMarchantia polymorphais regulated by a circadian clock

Abstract: 14The circadian clock coordinates an organism's growth, development and physiology with 15 environmental factors. One illuminating example is the rhythmic growth of hypocotyls and 16 cotyledons in Arabidopsis thaliana. Such daily oscillations in leaf position are often referred to as 17 sleep movements or nyctinasty. Here, we report that plantlets of the liverwort Marchantia 18 polymorpha show analogous rhythmic movements of thallus lobes, and that the circadian clock 19 controls this rhythm, with auxin a like… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…First, we co‐transformed sporelings with EF1 pro :amiR‐ Mp EFL MpMIR160 and a bioluminescence reporter for the Mp PRR promoter (Mp PRR pro : LUC ; Linde et al ., 2017) to complement previous studies on Mp LUX by testing the role of Mp EFL in regulation of the circadian clock. We observed fast damping of nyctinastic movements and Mp PRR pro : LUC signals, as well as elevated Mp PRR expression with attenuated amplitude, in the amiR‐ Mp EFL Mp MIR160 Mp PRR pro : LUC lines in LL, similar to previous observations for Mp lux ge (Figs S3, 3c; Lagercrantz et al ., 2020). Subsequently we used a bioluminescence approach to study the activity of a 4.4‐kb Mp DET1 promoter fragment in knock‐down plants of Mp LUX and Mp EFL .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…First, we co‐transformed sporelings with EF1 pro :amiR‐ Mp EFL MpMIR160 and a bioluminescence reporter for the Mp PRR promoter (Mp PRR pro : LUC ; Linde et al ., 2017) to complement previous studies on Mp LUX by testing the role of Mp EFL in regulation of the circadian clock. We observed fast damping of nyctinastic movements and Mp PRR pro : LUC signals, as well as elevated Mp PRR expression with attenuated amplitude, in the amiR‐ Mp EFL Mp MIR160 Mp PRR pro : LUC lines in LL, similar to previous observations for Mp lux ge (Figs S3, 3c; Lagercrantz et al ., 2020). Subsequently we used a bioluminescence approach to study the activity of a 4.4‐kb Mp DET1 promoter fragment in knock‐down plants of Mp LUX and Mp EFL .…”
Section: Resultsmentioning
confidence: 99%
“…This sampling has been described before (Lagercrantz et al, 2020). Growth and four-h-interval sampling of Tak-1 and the Mpprr ko mutant are also described in Lagercrantz et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1c,d). Molecular studies of the liverwort Marchantia polymorpha revealed characteristics of a circadian oscillator, as gene expression and thallus movement were rhythmic under constant light (Lagercrantz et al ., 2020). However, they appear to have lost the CCA1/LHY/RVE homolog and instead possess a single RVE3,4,5,6,8‐like homolog (Linde et al ., 2017) (Fig.…”
Section: The Origins Of Clock‐mediated Abiotic Stress Response In the Green Lineagementioning
confidence: 99%